Pengaruh Pendekatan CTL Terhadap Hasil Belajar Jaring-Jaring Bangun Ruang Sederhana Kelas V SD - Titin Rahmasari; Syafri Ahmad (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research was to effect of Contextual Teaching and Learning (CTL) approach on student learning outcomes in nets build a simple space V V group Kecamatan Sungai Tarab Kabupaten Tanah Datar, in the even semester of the academic year 2018/2019. This research is a quantitative research with experimental type and quasy experimental research design. Sampling data is taken by purposive sampling. Population of 72, with  sample of this study amounted to 40 people. Based on the research that has been done, obtained t count > t table, (2,02 > 1,72) with α = 0.05 is means Ho is rejected and Ha accepted, it meaning there is influence the use of Contextual Teaching and Learning (CTL) model of student learning outcomes in nets build a simple space V V group Kecamatan Sungai Tarab Kabupaten Tanah Datar.